Association of Blood Pressure Within 6 h After Endovascular Thrombectomy and Functional Outcomes in Ischemic Stroke Patients With Successful Recanalization - Zhang, Xuening; Cui, Ting; Zhu, Qiange; Wang, Changyi; Wang, Anmo; Yang, Yuan; Li, Shucheng; Hu, Fayun; Wu, Bo (Frontiers in Neurology, 2022)
Background and purpose: Blood pressure in the days following endovascular thrombectomy (EVT) can influence functional outcomes of patients who have suffered an acute ischemic stroke, but whether the same is true of blood pressure during the first few hours after EVT is unclear. Methods: Several blood pressure parameters were retrospectively analyzed in acute ischemic stroke patients who underwent EVT at West China Hospital from March 2016 to December 2019. Baseline blood pressure, speed of blood pressure reduction, postoperative blood pressure, degree of blood pressure reduction, and quality of blood pressure management were evaluated during the first 24 h after EVT. We explored whether these parameters during different time windows correlated significantly with patients’ modified Rankin Scale (mRS) score at 90 days. Results: Analysis of 163 patients showed that poor functional outcome (mRS scores 3-6) correlated significantly with higher postoperative blood pressure and worse blood pressure management during the first 6 h after EVT. Postoperative systolic blood pressure at 37 min after EVT was significantly higher in patients with poor outcome (141 mmHg) than in those with good outcome (mRS scores 0-2; 122 mmHg, p = 0.006), and systolic pressure >136 mmHg at this time point was associated with a significantly higher risk of poor outcome, before and after adjusting for other risk factors (adjusted OR 0.395, 95% CI 0.20-0.79). Conclusions: Among acute ischemic patients who successfully undergo recanalization, adequate blood pressure management during the first 30-40 min after EVT may be important for ensuring good 90-day functional outcomes.